Barriers and facilitators to fruit and vegetable consumption among rural Indian women of reproductive age - Kehoe, Sarah H.; Dhurde, Varsha; Bhaise, Shilpa; Kale, Rashmi; Gelli, Aulo (SAGE Publications, 2019)
Micronutrient deficiencies have been a serious public health problem among women of reproductive age in low- and middle-income countries including India, adversely affecting maternal and child health and human capital outcomes. Fruit and vegetables are important sources of micronutrients, and consumption of these foods is less than recommendations.